Rivaroxaban for thromboprophylaxis among patients recently hospitalized for acute infectious diseases: a subgroup analysis of the MAGELLAN study. (21st June 2018) - Cohoon, K. P.; De Sanctis, Y.; Haskell, L.; McBane, R. D.; Spiro, T. E.
Abstract : Essentials Net benefit of venous thromboprophylaxis (VTE) in patients hospitalized for infections is unknown. MAGELLAN trial subgroup analysis was performed for patients hospitalized for acute infectious diseases. At day 35, prolonged rivaroxaban prophylaxis reduced VTE compared to enoxaparin (4.2% vs. 6.6%). Rivaroxaban prophylaxis reduced VTE in patients hospitalized for active lung infections. Summary: Background: Despite the well‐established association between infection and venous thromboembolism (VTE), there are few data specifically assessing the efficacy and safety of the VTE prophylaxis strategies for patients hospitalized for acute infectious diseases. Objectives: To estimate the incidence of VTE and bleeding outcomes, comparing prolonged prophylaxis with rivaroxaban 10 mg daily for 35 days with enoxaparin 40 mg daily for 10 days. Patients/Methods: A subgroup analysis of patients hospitalized for acute infectious diseases in the MAGELLAN trial was performed. The primary efficacy outcome was the composite of asymptomatic proximal or symptomatic VTE at days 10 and 35. The principal safety outcome was the composite of major or clinically relevant non‐major bleeding. Results: Three thousand one hundred and seventy‐three patients with acute infectious diseases leading to hospitalization were randomized to either rivaroxaban ( n = 1585) or enoxaparin/placebo ( n = 1588), and received at least one dose of study medication. At day 10, primary composite efficacy outcomes did not differ between prophylaxis strategies (rivaroxaban, 2.7%; and enoxaparin, 3.7%). At day 35, there were fewer VTE events with rivaroxaban (4.2%) than with enoxaparin (6.6%) (relative risk [RR] 0.64; 95% confidence interval [CI] 0.45–0.92). Patients with pulmonary infections randomized to rivaroxaban had a lower incidence of VTE both at 10 days (RR 0.50, 95% CI 0.28–0.90) and at 35 days (RR 0.54, 95% CI 0.33–0.87). Primary safety outcome events were increased with rivaroxaban (RR 2.42, 95% CI 1.60–3.66). Conclusions: Prolonged rivaroxaban prophylaxis reduced the incidence of VTE in patients hospitalized for acute infectious diseases, particularly those involving the lungs. Efficacy benefits were, in part, offset by bleeding outcomes. ClinicalTrials.gov Number: NCT 00571649.